Pregnancy in an Infertile Woman with Polycystic Ovary Syndrome - Islam, Md Imtiajul; Ali, Md Zulfikar; Hoque, Sayama (KYAMC Journal, 2017)
Introduction: The most common cause of anovulatory infertility is polycystic ovary syndrome (PCOS). It is a syndrome of ovarian dysfunction associated with hyperandrogenism and polycystic ovary morphology. Several treatment options are available for women with infertility related to PCOS including weight reduction, clomiphene citrate, gonadotropins, laparoscopic ovarian diathermy, metformin and letrozole. Case Presentation: This is a case report of 32-year-old infertile female who was married for 12 years and tried ovulation induction drugs several times but failed to conceive. She was overweight, hirsute, oligomenorrheic and lastly amenorrheic. Investigations revealed altered ratio of FSH and LH, and polycystic ovaries on ultrasound. Patient was adviced to do regular physical exercise and prescribed metformin and combined oral contraceptive pill. After treatment restoration of regular menstruation occurred, weight reduced and patient became pregnant. Conclusion: Before choosing any treatment option for an infertile woman with PCOS proper control of abnormal metabolic conditions are necessary for a successful treatment outcome. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 656-659